IMPLIKASI PEMBERITAAN LESBIAN GAY BISEKSUAL TRANSGENDER (LGBT) PADA AKTIVITAS LEMBAGA SWADAYA MASYARAKAT - Denada Faraswacyen L. Gaol (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
This study aims to determine the implications of LGBT news on the activities of NGOs as follows: Arus Pelangi, Inter Medika Foundation and Yayasan Srikandi Sejati by using the case study method, with primary data collected through interview with key informants from the three NGOs and analyzed with the Theory of Cognitive Dissonance. Numerous coverage mainly those telling the negative treatment towards LGBT triggers various forms of defense and protection in the name of humanity and human rights. The results of this study indicate that LGBTs who are considered incompatible with the cultural and social norms prevailing in society have the rights to receive social support. Social support provided by Arus Pelangi covers program campaigning on the socialization of basic human rights and the eliminaton of discriminatory action on LGBT and advocacy which are the casuistic and the one on public policy. Casuistic advocacy is a legalJurnal Avant Garde Volume 4 Nomor 2 Desember 2016 18activity on cases of litigation and non-litigation affecting LGBT. Advocacy on public policy is a series of legal actions against all discriminatory government policies, for example is the rejection of the Bill on Anti-Pornography and Porn Actions (RUU-APP). Inter Medika Foundation and Yayasan Srikandi Sejati are NGOs that focus on health assistance or counseling, for examples are on issues of sexually transmitted diseases and prevention of the spread of HIV/AIDS among LGBTs, by having cooperation with the local government and several hospitals in Jakarta.